Merchant Capital, the State, and Labour in a British Colony: Servant-Master Relations and Capital Accumulation in Newfoundland’s Northeast-Coast Fishery, 1775-1799 - Cadigan, Sean (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1991)
AbstractThis paper uses a case study of class struggle in the late-eighteenth-century Newfoundland fishery to examine the relationship between merchant capital and the employment of wage labour in staple production in early colonial development. Using a modified version of the staple model which emphasises the role of the class relations and institutional structures of staple industries on long-term development, it finds that British regulation of wages to protect the migratory fishery stymied the extensive employment of wage labour by resident planters. Evidence drawn from court records suggests that fishing servants used the law to prevent erosion of wages due from planters at the end of a fishing season by ignoring mandatory preseason contracts or account overcharges. Servants enjoyed less, but still formidable, success in winning suits brought about by masters for neglect. By using wage law beyond the intentions of its British makers, servants forced planters increasingly to rely on family labour rather than wage labour. The struggles of wage labourers with their employers, rather than merchant conservatism as such, contributed to Newfoundland's long-term domination by merchant truck with fishing families.